MOTIF ORGANIZATIONAL CITIZENSHIP BEHAVIOR PENGURUS HIMPUNAN MAHASISWA JURUSAN DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MEDAN - Abdul Murad; Asih Menanti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to determine the level of OCB motives for HMJ FIP Unimed administrators. This research is a quantitative descriptive research that is ex post facto. The study was conducted on samples taken in total from the research population totaling 115 students of HMJ FIP Unimed management. OCB motif data collection uses a Likert scale and data analysis uses calculations that are not generalizations, but apply to research subjects. The results showed that the overall OCB motive of HMJ-HMJ administrators at FIP UNIMED was at a sufficient level. Based on the aspects of the OCB motive, it is known that the OCB motive in the prosocial aspect and the concern for the organization of HMJ FIP Unimed is of low level, while in the aspect of impression management it is at a sufficient level.